The Role of Graphic Design in Spreading Environmental Awareness (Al-Academy, 2025)
The environment is the spatial space and vital field in which a person lives, and whose life depends on its natural resources, Therefore, it has become necessary and obligatory to preserve, protect and develop these natural resources through laws, regulations, sound practices and positive behaviors and develop them in a way that achieves sustainable development of the environment, One of the important media means is posters, which play an important role in spreading environmental awareness among individuals and society in general. Hence the research problem came through the following question: What is the role of graphic design in spreading environmental awareness in society?The aim of the research is to identify the role of graphic posters in spreading environmental awareness and developing positive behavior in society. The descriptive analytical method was used in analyzing the samples that were selected according to the available sampling method, and the research reached the most important results: the posters played an important role in conveying the communication message to the community, The designs of the researched posters were distinguished by the simplicity and ease of design and the depth of meaning and content in the presentation to educate society about the dangers of environmental pollution. The authors concluded that developing well-thought-out plans to raise environmental awareness and protect it through the use of multiple methods is a fundamental step toward achieving a sustainable environment. Community and international organizations play a crucial role in spreading this awareness and promoting environmental conservation practices. Graphic design is also an influential communication tool that contributes to changing the behavior and ideas of communities and their individuals, leading to the protection of lives and ensuring public health. This positively impacts the development of income sources and the improvement of economic, social, and health aspects. Furthermore, the importance of enacting laws and legislation criminalizing environmental abuse and unsound practices is crucial, providing a legal environment that supports sustainability. Finally, adopting clean energy solutions represents a vital path to protecting the environment and achieving sustainable development across all sectors. The research recommends the necessity of enacting laws and legislation that are concerned with various environmental topics and paying attention to graphic design and posters in general because of its importance in delivering communication messages to the public and society and creating sustainable environmental awareness, and the necessity of supporting organizations and associations specialized in protecting the environment and in a way that achieves sustainable development in the environment and society.